2017
DOI: 10.2147/ijgm.s129075
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the outcomes of elderly hospitalized myasthenia gravis patients: a national database study

Abstract: BackgroundMyasthenia gravis (MG) in elderly populations is increasing. This study aimed to evaluate predictors for treatment outcomes in elderly hospitalized MG patients using the national database.MethodsWe collected data of elderly hospitalized MG patients from the National Health Security Office from October 2009 to September 2010. Predictors for treatment outcomes were examined.ResultsDuring the study period, 1,948 identified MG patients were admitted to hospitals throughout Thailand. Of those, 441 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…C5.0 is a promising ML-based decision tree algorithm and has been successfully used in clinical/healthcare issues [26,53]. Previously published predictive factors of the prognosis of MG in MG deterioration, severity, and hospital stay have used multivariable logistic regression analyses [49,54,55]. This research found that, compared with LR, C5.0 and the other two ML-based decision tree algorithms can generate a better accuracy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…C5.0 is a promising ML-based decision tree algorithm and has been successfully used in clinical/healthcare issues [26,53]. Previously published predictive factors of the prognosis of MG in MG deterioration, severity, and hospital stay have used multivariable logistic regression analyses [49,54,55]. This research found that, compared with LR, C5.0 and the other two ML-based decision tree algorithms can generate a better accuracy.…”
Section: Discussionmentioning
confidence: 98%
“…Other large cohort studies suggested that late-onset MG patients are prone to increased disease severity, and the mortality rate increased in the elderly [15,48]. This is because elderly patients with MG tend to have comorbidities and complications, such as sepsis, resulting in long hospital stays and high costs [49]. Old onset age of MG could be associated with an increased susceptibility to autoimmune diseases, due to immune dysregulation and increased inflammatory background that can cause a high production of autoantibodies [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 These conditions are increasingly recognized as a consequence of more availability and accessibility of biomarker testing, although there is scarce epidemiological data from this region. [5][6][7] Early treatment of acute attacks is crucial to prevent mortality and long-term disabilities, especially in neuromyelitis optica spectrum disorder (NMOSD), acute inflammatory demyelinating polyneuropathy (AIDP), and autoimmune encephalitis. [8][9][10] However, several obstacles prevent neurologists from accessing and prescribing TPE.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors have been reported to be associated with myasthenia gravis (MG) prognosis. For example, in patients with late‐onset MG (>60 years of age), clinical factors such as concomitant pneumonia and sepsis, as well as introduction of mechanical ventilation, have been associated with poor MG outcomes 1 . In contrast, early onset (<40 years of age) is reportedly associated with complete stable remission (CSR) status (ie, good outcomes) on the Myasthenia Gravis Foundation of America Post‐Intervention Status (MFGA‐PIS) scale 2 .…”
Section: Introductionmentioning
confidence: 99%